Japan : Staff Report for the 2004 Article IV Consultation. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2004)
This 2004 Article IV Consultation highlights that Japan's economic recovery continued in 2003 and into the first part of 2004. For 2003, GDP growth reached 2 1\2 percent, double the mid-year consensus forecast, and continued at about 6 percent on an annualized basis in the first quarter of 2004. As the economic recovery broadens further, real GDP is projected to expand by 4 1\2 percent in 2004 and 2 1\2 percent in 2005, with CPI deflation ebbing to zero by the end of this period.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet